Modelo alométrico para estimar la altura total de las especies forestales del bosque de colina baja de la concesión forestal 16-LOR-MAY/CON-MAD-2019-018, distrito del Napo, Loreto, 2022 - Cueva Echevarria, Leydi Ester (2023)
The allometric model was determined to estimate the total height of the forest species of the lower hill of the forest concession 16-LOR-MAY/CON-MAD-2019-018, district of Napo, Loreto, Peru. The forest census data of the commercial species of the operational plan (PO) 1 of the PC 1 cutting plot for forest use permits was evaluated. The results indicate that 12 273 trees were registered, grouped into 52 commercial forest species and 22 botanical families. The average total diameter-height relationship of the trees was adjusted to the distribution model of the cubic type (Y = 39,750 + (-0,582 x DAP) + (0,006 x DAP2) + (-2,007E-5 x DAP3)), with a correlation coefficient of r=0,967 and a determination coefficient of R2=0,935. The hypothesis is rejected in the sense that the linear allometric model did not fit the relationship between the diameter and the total height to estimate the height of the trees of the low hill forest.